Homeward bound American families in the Cold War era - May, Elaine Tyler 1947- (Basic Books, 2017)
When Homeward Bound initially appeared, it forever changed how we understand Cold War America. Previously, scholars understood the post-World War II era as a time when Americans turned away from politics to enjoy the fruits of peace and prosperity after decades of depression and war, while their leaders remained preoccupied with the Soviet threat and the dangers of the Atomic Age. Elaine Tyler May challenged the idea of an apolitical private arena, demonstrating that the Atomic Age and the Cold War were not merely the concerns of experts and policy makers but infused American life at every level, from the boardroom to the bedroom
Keywords: Geschichte 1950-1960; Auswirkung; Elfter September; Familie; USA; Families / United States / History / 20th century; Baby boom generation / United States; United States / Social conditions / 1945-; Familles / États-Unis / Histoire / 20e siècle; Génération du baby-boom / États-Unis; États-Unis / Conditions sociales / 1945-; Baby boom generation; Families; Social conditions; United States / https://id.oclc.org/worldcat/entity/E39PBJtxgQXMWqmjMjjwXRHgrq; États-Unis / Conditions sociales / 1945-....; Since 1900; History